Leadership behaviour and university culture associated with leadership effectiveness for academic work in Malaysian Public universities - Gan, Siew Ling. (Universiti Malaysia Sarawak, (UNIMAS), 2009)
This study examined the leadership behaviour and university culture associated with leadership effectiveness for academic work in Malaysian public universities. Using a cross-sectional survey research design, the data for the study was collected from 420 academic staff in 20 public universities in Malaysia using questionnaire. The questionnaire consisted of four sections comprising a demographic section, and three sections which measures leadership behaviour, university culture, and leadership effectiveness for academic work of vice-chancellors (VCs) and deputy vice-chancellors (DVCs). The findings indicated that the academic staff perceived their vice-chancellor's and deputy vice cancellors' behaviours as more toward managing process rather than focusing on relating to people. This implied that vice-cancellor and deputy vice-cancellors in Malaysian public Universities were task-oriented leaders.